Os determinantes do endividamento público dos municípios do Estado do Ceará: uma análise econométrica - Oliveira, Fabiana Helcias (2014)
The Fiscal Responsibility Law emerges as a way to discipline public spending and debt control, although, it is clear the indebtedness is still a feature of Municipalities. This research aimed to verify which indicators are critical for indebtedness of municipalities in Ceará. Therefore, an econometric model was developed, covering 184 municipalities from 2001 to 2012, to analyse whether other authors had already studied these financial indicators and if other variables called behavioral "policies" are determinants of public debt. The results indicate the capital structure is the most important variable for the clarification of municipal indebtedness. The results also suggest that the variable "personnel expenses", "spending on public investment", "re-election" and "election" have positive connection with public indebtedness, but little influence. The financial variable “liquidity” and the behavioral ones,"political", gender, age and education level of the manager, were not statistically significant.The degree of dependence resulted negatively related to the public debt, and with low explanatory power. Right-wing-party managers are more conservative and tend to present a negative index of significance. The results of this research are restricted to the municipalities of Ceará, studied period and chosen variables.